In vitro activity of cefiderocol and comparators against isolates of Gram-negative pathogens from a range of infection sources: SIDERO-WT-2014–2018 studies in Italy. (June 2021) - Stracquadanio, Stefano; Torti, Eleonora; Longshaw, Christopher; Henriksen, Anne Santerre; Stefani, Stefania
Highlights: A total of 2472 clinical Gram-negative bacterial isolates from Italy were investigated. Cefiderocol was active in vitro against a wide range of carbapenem-resistant Gram-negative pathogens. Susceptibility rates for cefiderocol against non-fermenter species were high (>95%). 6.2% of Enterobacterales and 55.7% of non-fermenter isolates were meropenem-resistant. Cefiderocol retained activity against meropenem-resistant Gram-negative isolates. ABSTRACT: Objectives: : Antimicrobial resistance, particularly carbapenem resistance, in Gram-negative pathogens poses a significant healthcare threat. Carbapenem resistance rates in Italy are among the highest in Europe. We report the in vitro activity of cefiderocol, a novel siderophore cephalosporin, and comparator antibiotics against Gram-negative isolates from Italy as part of the SIDERO-WT studies. Methods: : Isolates were collected between 2014 and 2018. Minimum inhibitory concentrations (MICs) were determined using International Organization for Standardization and EUCAST guidelines. Antimicrobial susceptibilities were interpreted using EUCAST breakpoints; pharmacodynamic/pharmacokinetic breakpoints were used if EUCAST breakpoints were not specified. Results: : The 2472 isolates [1545 (62.5%) Enterobacterales and 927 (37.5%) non-fermenters] represented a range of infection sources, including nosocomial pneumonia (902; 36.5%), complicated urinary tract infection (374; 15.1%), bloodstream infection (596; 24.1%), complicated intra-abdominal infection (257; 10.4%) and other infection sources (343; 13.9%). Cefiderocol was active against the majority of isolates, regardless of infection source (susceptibility, 94.2−97.3%). A high proportion of non-fermenters (97.6%) and Enterobacterales (95.6%) were cefiderocol-susceptible, although susceptibility was lower in Klebsiella pneumoniae (88.1%). Susceptibility to cefiderocol was significantly ( P < 0.01) greater than comparators overall (96.4% vs. 71.3–81.6%) and in non-fermenters (97.6% vs. 44.3–90.3%) across infection sources. Overall 612/2472 isolates (24.8%) were meropenem-resistant (MIC > 8 mg/L), comprising 516/927 (55.7%) non-fermenters and 96/1545 (6.2%) Enterobacterales. Cefiderocol (499/516; 96.7%) activity was greater than colistin (440/516; 85.3%), ceftazidime/avibactam (123/516; 23.8%) and ceftolozane/tazobactam (89/516; 17.2%) in meropenem-resistant non-fermenter isolates. Conclusion: : Susceptibility to cefiderocol was significantly greater than meropenem, colistin, ceftazidime/avibactam and ceftolozane/tazobactam overall, regardless of infection source. Graphical abstract: Image, graphical abstract